Correction: Patil et al. Freeing Aspergillus fumigatus of Polymycovirus Infection Renders It More Resistant to Competition with Pseudomonas aeruginosa Due to Altered Iron-Acquiring Tactics. J. Fungi 2021, 7, 497 - Patil,RH; Kotta-Loizou,I; Palyzová,A; Pluháek,T; Coutts,RHA; Stevens,DA; Havlíek,V (Journal of Fungi, 2022)
In the original publication [...].